CRISPR/Cas9 Genome-Editing System in Human Stem Cells: Current Status and Future Prospects - Zhao Zhang; Yuelin Zhang; Fei Gao; Shuo Han; Kathryn S. Cheah; Hung-Fat Tse; Qizhou Lian (Elsevier, 2017)
Genome-editing involves the insertion, deletion, or replacement of DNA in the genome of a living organism using "molecular scissors." Traditional genome editing with engineered nucleases for human stem cells is limited by its low efficiency, high cost, and poor specificity. The CRISPR system has recently emerged as a powerful gene manipulation technique with advantages of high editing efficiency and low cost. Although this technique offers huge potential for gene manipulation in various organisms ranging from prokaryotes to higher mammals, there remain many challenges in human stem cell research. In this review, we highlight the basic biology and application of the CRISPR/Cas9 system in current human stem cell research, discuss its advantages and challenges, and debate the future prospects for human stem cells in regenerative medicine.